Predicting demand: what is world class and what is worst-in-class - Fugate, Brian S. (Henry Stewart Talks, 2010)
Benchmarking Studies, Forecasting Process Dimensions, Four Stages of Forecasting Management, Specific discussion on each stage for each forecasting dimension, The impact of forecasting process improvements on shareholder value